Factors associated with viral suppression and rebound in children and adolescents living with HIV on antiretroviral treatment at the Bangui pediatric complex, Central African Republic - Henri, Diemer Saint Calvaire; Dieu, Longo Jean de; Sylvain, Woromogo Honoré; Simplice, Kango; Grésenguet, Gérard (International Journal Of Community Medicine And Public Health, 2023)
Background: Suppression of viral load and its maintenance is the necessary condition for reducing mortality linked to HIV infection in children. This study aimed to investigate the factors associated with viral load rebound in children receiving antiretroviral treatment. Methods: This was a cross-sectional study with analytical purposes, running from August 1 to 31, 2023. Were inclusive, all children living with HIV under 15 years of age, with at least two viral load results and whose parents have agreed to participate in the study. Results: A total of 286 children were included in the study. The mean age was 11.5 years (±2.8). More than half (55.2%) of the children were not informed of their HIV status and for the majority (50.3%). Among the 198 children with a suppressed viral load at the first test, 46 (23.2%) experienced a rebound in viral load at the last test. The factors significantly associated with rebound were the low level of education of the parents (p=0.012), the administration of medicines to the children by the parents (p=0.000), the long duration of taking the medicines (p=0.021) and poor compliance with treatment (0.000). Conclusions: The rebound in viral load after suppression is a disastrous reality for children. Efforts must be made to strengthen early therapeutic education for children, training of health workers on the process of announcing results and ongoing dialogue with children and adolescents on compliance are ways to improve the maintenance of viral suppression.